POTENSI PENGEMBANGAN TANAMAN JAGUNG (Zea mays L.) BERDASARKAN KESESUAIAN SIFAT FISIK TANAH DI KABUPATEN PANGKEP - Khaeriah, Miftahul; Nurmiaty, Nurmiaty; Junaedi, Junaedi (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
This research aims to analyze the level of suitability of land physical properties for the development of corn plants in Pangkep Regency. The method used is by collecting administrative maps in Pangkep Regency. The technique used is by using the Arc-GIS processing tool, digital land system data is cut with the administrative map of Pangkep Regency to obtain a land data system for Pangkep Regency. Data on the physical characteristics of Pangkep Regency were extracted from the Pangkep Regency land system data to obtain data and maps of the physical characteristics of the Pangkep Regency area. Then analyze the physical characteristics of the soil for the suitability of corn plants for the suitability of each physical characteristic of the soil in Pangkep Regency with the requirements for growing corn plants based on the criteria of the Ministry of Agriculture's Research and Development Center. Conclusions that can be drawn from this research are: 1. There is land with a very suitable land suitability class (S1) for the development of corn plants with a total area of 29,641ha spread across every sub-district in Pangkep Regency.2. There is land with a moderately suitable land suitability class (S2) with a total area of 3,730 ha and a marginally suitable land suitability class (S3) with a total area of 17,903 ha for corn crops in Pangkep Regency. 3 There is land with an unsuitable land suitability class (N) with a total area of 27,754 ha which has severe inhibiting factors so that it cannot be used as a location for developing corn plants in Pangkep Regency.